Fana wegi yelewt aqenqagnoch be Ityopia : bahayangaw meto amet mebacha - Bahru Zewde (Addis Ababa University Press; Addis Ababa, Ethiopia, 2013)
On Ethiopian change activists in the begining of the 20th century.
100- Bahiru Zewdu [Zewdie] 245- Fana wegi yelewt akenkanoch beItyopia [Ityopya] : behayegnaw amet mebacha /Bahiru Zewdie [Zewde]
Includes bibliographical references (pages [303]-326) and index.
In Amharic.